In Vitro Activity of 3 Commercial Bacteriophage Cocktails Against Salmonella and Shigella spp. Isolates of Human Origin - Odette J. Bernasconi; Valentina Donà; Regula Tinguely; Andrea Endimiani (Case Western Reserve University, 2018)
Background: Salmonella and Shigella spp. are 2 of the most frequent and deadly enteric bacterial pathogens recorded worldwide. In developing countries Salmonella infections are responsible for many deaths annually and these mortality rates are prone to increase due to the emergence of resistance to antibiotics. In this overall scenario new alternative therapeutic approaches are needed. Methods: For the first time, we investigated the activity of 3 commercial bacteriophage cocktails (INTESTI, Septaphage, PYO) against a collection of contemporary Salmonella spp. (n = 30) and Shigella spp. (n = 20) strains isolated in Switzerland. Phage susceptibility was determined by implementing the spot test. Results: The overall susceptibility of Salmonella spp. to INTESTI and Septaphage was 87% and 77%, respectively. With regard to Shigella spp., the overall susceptibility to INTESTI and Septaphage was 95% and 55%, respectively. PYOwas observed to be active against only 10% of Salmonella spp. but against 95% of Shigella spp. Conclusions: Our results seem promising, especially for the INTESTI biopreparation against Salmonella enterica infections. Nevertheless, such speculation should be supported by further in vivo studies to confirm efficacy and safety of the cocktails. We also emphasize the importance of large in vitro screening analyses aimed to assess the activity of such biopreparations against contemporary multidrug-resistant strains that are emerging worldwide. Keywords: commercial; bacteriophages; Salmonella; Shigella cocktails